2015
DOI: 10.1155/2015/806979
|View full text |Cite
|
Sign up to set email alerts
|

The Place of Dipeptidyl Peptidase-4 Inhibitors in Type 2 Diabetes Therapeutics: A “Me Too” or “the Special One” Antidiabetic Class?

Abstract: Incretin-based therapies, the most recent therapeutic options for type 2 diabetes mellitus (T2DM) management, can modify various elements of the disease, including hypersecretion of glucagon, abnormal gastric emptying, postprandial hyperglycaemia, and, possibly, pancreatic β cell dysfunction. Dipeptidyl peptidase-4 (DPP-4) inhibitors (gliptins) increase glucagon-like peptide-1 (GLP-1) availability and correct the “incretin defect” seen in T2DM patients. Clinical studies have shown good glycaemic control with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
58
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 278 publications
5
58
0
4
Order By: Relevance
“…In this way, incretin-based therapies based on the oral administration of DPP-IV inhibitors (gliptins) are the most recent alternative treatments of T2DM as recently reviewed (Godinho et al, 2015). Nowadays, numerous works have focused on the strategy to identify "natural" peptide inhibitors of DPP-IV activity as an alternative for synthetic drugs to restore the incretin effect in T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, incretin-based therapies based on the oral administration of DPP-IV inhibitors (gliptins) are the most recent alternative treatments of T2DM as recently reviewed (Godinho et al, 2015). Nowadays, numerous works have focused on the strategy to identify "natural" peptide inhibitors of DPP-IV activity as an alternative for synthetic drugs to restore the incretin effect in T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…They have no effect on body weight and they are safe with respect to causing hypoglycemia. 151 The various DPP4 inhibitors are similar concerning their antihyperglycemic properties. 151 Regarding the effectiveness of DPP4 in reducing postprandial hyperglycemia compared to other hypoglycemic agents targeting postprandial glucose, a recent study in 19 type 2 diabetics inadequately controlled by diet and exercise indicated that the effects of sitagliptin on postprandial glucose levels were similar to those of nateglinide.…”
mentioning
confidence: 99%
“…151 The various DPP4 inhibitors are similar concerning their antihyperglycemic properties. 151 Regarding the effectiveness of DPP4 in reducing postprandial hyperglycemia compared to other hypoglycemic agents targeting postprandial glucose, a recent study in 19 type 2 diabetics inadequately controlled by diet and exercise indicated that the effects of sitagliptin on postprandial glucose levels were similar to those of nateglinide. 152 Pramlitidine is a synthetic analog of amylin which may be used with mealtime insulin in type 1 and type 2 diabetic patients.…”
mentioning
confidence: 99%
“…An intensive glycemic control led to reduced microvascular complications, especially retinopathy and nephropathy, but had only a modest effect on macrovascular complications [3]. However, in addition to effects on pancreas function, the effects on other organs/tissues that are involved in T2DM complications, such as heart, kidney, and retina, have been increasingly reported [4]. It has become clear that in subjects with diabetes not only dysglycemia should be treated but also macrovascular and microvascular complications should be prevented and cared for.…”
mentioning
confidence: 99%